150 years of new beetles (Coleoptera) described in The Canadian Entomologist and associated publications (1868–2017). Issue 6 (24th October 2018) - Bouchard, P.; Brunke, A.J.; Davies, A.E.; Douglas, H.; Smith, A.B.T.; Manoogian, J.
Abstract: The Canadian Entomologist and its associated publications ( Supplements of The Canadian Entomologist and Memoirs of the Entomological Society of Canada ) have served as important outlets for taxonomic contributions on arthropods since 1868. A survey of beetle (Coleoptera) publications therein has revealed that 2276 species-group, 136 genus-group, and seven family-group taxa were first described in 492 scientific articles. New beetles were described in 67 families by 165 authors. We document trends of beetle descriptions over time, by taxonomic group and by the origin of the new taxa. We also provide biographical notices of the entomologists who described the new taxa. We believe that The Canadian Entomologist will continue to be coveted as a suitable outlet for taxonomic works in the future.